The Role of Health Worker in Performing Medical Services during Post Pandemic - Joseph Haddad (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Though have seems to reach the beginning of the end of the COVID-19 pandemic, there are still looming problems on the horizon. There are necessary adjustments needed with an end goal of supporting the ongoing COVID-19 response while at the same time strengthening our resilience and capacity to respond to public health emergencies in the future.The safety of health care workers (HCW) is an utmost priority and needs to be sustained; WHO has continuously called on governments and health care leaders to address the persistent threats to the health and safety of health workers and patients since the beginning of the pandemic. “The COVID-19 pandemic has reminded all of us of the vital role health workers play to relieve suffering and save lives,” said Dr Tedros Adhanom Ghebreyesus, WHO Director-General. “No country, hospital or clinic can keep its patients safe unless it keeps its health workers safe and ensuring that health workers have the safe working conditions, the training, the pay and the respect they deserve.